Flow injection chemiluminescence determination of tetracycline - Alan Townshend (2018)
A simple flow injection chemiluminometric method for the determination of tetracycline (TC), chlortetracycline (CTC) or oxytetracycline (OTC) has been developed. The method is based on the chemiluminescence (CL) produced the reduction by these tetracyclines of tris(2,2′-bipyridyl)ruthenium(III). The latter is obtained by oxidation of tris(2,2′-bipyridyl)ruthenium(II) by potassium permanganate in dilute nitric acid. A standard or sample solution is injected into the ruthenium(II) stream either before or after it has merged with the potassium permanganate stream. The CL intensity is increased by the presence of manganese(II). Under the optimum conditions, calibration graphs were obtained for 5 × 10-5to 5 × 10-4mol l-1of each tetracycline. The detection limits (s/n = 3) were 2.0 × 10-6, 1.9 × 10-6and 1.0 × 10-6mol l-1, respectively, and mid-calibration range standard deviations were not greater than 3.7% (n = 10). The method was successfully applied to the determination of these drugs in pharmaceutical formulations with a sample throughput of 50 h-1. © 2004 Elsevier B.V. All rights reserved.